Improving, Restoring, and Managing Natural Resources on Rural Properties in Florida: Sources of Financial Assistance - Chris Demers; Martin B. Main; Mark E. Hostetler (EDIS)
Revised! SS-FOR-23, a 10-page fact sheet by Chris Demers, Martin B. Main, and Mark E. Hostetler, inform landowners about government programs available to help conserve natural resources. Includes references. Published by the UF School of Forest Resources and Conservation, September 2009.